Achieving a person‐centered approach to dialysis discontinuation: An historical perspective. Issue 5 (10th April 2019) - O'Hare, Ann M.; Murphy, Emma; Butler, Catherine R.; Richards, Claire A.
Abstract: In this essay, we describe the evolution of attitudes toward dialysis discontinuation in historical context, beginning with the birth of outpatient dialysis in the 1960s and continuing through the present. From the start, attitudes toward dialysis discontinuation have reflected the clinical context in which dialysis is initiated. In the 1960s and 1970s, dialysis was only available to select patients and concerns about distributive justice weighed heavily. Because there was strong enthusiasm for new technology and dialysis was regarded as a precious resource not to be wasted, stopping treatment had negative moral connotations and was generally viewed as something to be discouraged. More recently, dialysis has become the default treatment for advanced kidney disease in the United States, leading to concerns about overtreatment and whether patients' values, goals, and preferences are sufficiently integrated into treatment decisions. Despite the developments in palliative nephrology over the past 20 years, dialysis discontinuation remains a conundrum for patients, families, and professionals. While contemporary clinical practice guidelines support a person‐centered approach toward stopping dialysis treatments, this often occurs in a crisis when all treatment options have been exhausted. Relatively little is known about the impact of dialysis discontinuation on the experiences of patients and families and there is a paucity of high‐quality person‐centered evidence to guide practice in this area. Clinicians need better insights into decision‐making, symptom burden, and other palliative outcomes that patients might expect when they discontinue dialysis treatments to better support decision‐making in this area.